Penetration of sub-micron particles into dentinal tubules using ultrasonic cavitation. (January 2017) - Vyas, N.; Sammons, R.L.; Pikramenou, Z.; Palin, W.M.; Dehghani, H.; Walmsley, A.D.
Abstract: Objectives: Functionalised silica sub-micron particles are being investigated as a method of delivering antimicrobials and remineralisation agents into dentinal tubules. However, their methods of application are not optimised, resulting in shallow penetration and aggregation. The aim of this study is to investigate the impact of cavitation occurring around ultrasonic scalers for enhancing particle penetration into dentinal tubules. Methods: Dentine slices were prepared from premolar teeth. Silica sub-micron particles were prepared in water or acetone. Cavitation from an ultrasonic scaler (Satelec P5 Newtron, Acteon, France) was applied to dentine slices immersed inside the sub-micron particle solutions. Samples were imaged with scanning electron microscopy (SEM) to assess tubule occlusion and particle penetration. Results: Qualitative observations of SEM images showed some tubule occlusion. The particles could penetrate inside the tubules up to 60 μm when there was no cavitation and up to ∼180 μm when there was cavitation. Conclusions: The cavitation bubbles produced from an ultrasonic scaler may be used to deliver sub-micron particles into dentine. This method has the potential to deliver such particles deeper into the dentinal tubules. Clinical significance: Cavitation from a clinical ultrasonic scaler may enhance penetration of sub-micron particles into dentinal tubules. This can aid in the development of novel methods for delivering therapeutic clinical materials for hypersensitivity relief and treatment of dentinal caries.